2020
DOI: 10.12669/pjms.36.4.2400
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Awareness of Risk Factors of Non-Communicable Diseases among University Students in Saudi Arabia

Abstract: Background and Objective: Non-communicable diseases (NCDs) are the leading cause of morbidity and mortality in developed countries. This study has evaluated the frequency of the risk factors of NCDs and its awareness among students in a University in Saudi Arabia. Methods: This cross-sectional study was conducted among 374 female students of Prince Sattam bin Abdulaziz University in Wadi Al Dawaser, Saudi Arabia. The study was carried out for a duration of six months, from August 2019 to January 2020. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
(13 reference statements)
3
8
0
Order By: Relevance
“…The current study is consistent with a study from Rwanda (35.0%) (21). However, the prevalence of the current study is lower than the studies from Bangladesh (57.9%) (12), Spain (46.7%) (13), Saudi Arabia (43.8%) (14), and Sri Lanka (43%) (15). The variation might be due to differences in the study population, sampling techniques, and sociodemographic characteristics.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study is consistent with a study from Rwanda (35.0%) (21). However, the prevalence of the current study is lower than the studies from Bangladesh (57.9%) (12), Spain (46.7%) (13), Saudi Arabia (43.8%) (14), and Sri Lanka (43%) (15). The variation might be due to differences in the study population, sampling techniques, and sociodemographic characteristics.…”
Section: Discussionsupporting
confidence: 88%
“…Concerning knowledge of NCDs, studies conducted among diverse populations in different countries have revealed varying levels of knowledge of NCDs. Accordingly, a good level of knowledge was reported to be 81.2% in Malaysia ( 11 ), 57.9% in Bangladesh ( 12 ), 46.7% in Spain ( 13 ), 43.8% in Saudi Arabia ( 14 ), 43% in Sri Lanka ( 15 ), 27.7% in Malaysia ( 16 ), 25% in China ( 17 ), and 12.5% in Myanmar ( 18 ). Furthermore, a finding from China indicates chronic diseases knowledge varied from 29.5 to 90.2% ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, introducing positive health-related behaviors and detecting hazards at a young age will have a significant impact on the adaptation of healthy behaviors that will last throughout adulthood (WHO, 2020; NCD Surveillance Toolkit from the Pan American Health Organization (PAHO) 2) STEP-wise approach-to-Surveillance (STEPS) of NCD risk factors questionnaire developed by the WHO. In addition to 100% reports of junk food consumption, the survey found a high frequency of physical inactivity (Rahamathulla and Mohemmed, 2020). Only two studies on medical students have been carried out in KSA to our knowledge.…”
Section: Medical Science L Analysis Articlementioning
confidence: 89%
“…According to the Ministry of Health (MOH) in KSA, NCD treatment accounts for 65 % of healthcare spending. Furthermore, the Saudi MOH is working tirelessly to lower the prevalence of NCDs by establishing health strategies and programs as part of the country's overall development strategy (Rahamathulla and Mohemmed, 2020). NCDs have also been included in the United Nations 2030 Agenda for Sustainable Development, which aims to reduce the number of premature deaths caused by NCDs by a third by 2030 (WHO, 2020; Alzahrani et al, 2019;Martinez-Lacoba et al, 2018).…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%
“…According to the study done on University students in Saudi Arabia respondent's knowledge was not good, but they had a good attitude. They were unaware of few important factors implicated in the CVD, like stress, diabetes mellitus, chronic renal failure, increased use of salt, excessive use of organ meat such as liver, kidney, and brain, sedentary lifestyle, waist circumference >40 inches, BMI >30 (Rahamathulla et al, 2020).…”
Section: Background Of the Studymentioning
confidence: 99%